Transient thermo-solutal convection in a tilted porous enclosure heated from below and salted from above. (November 2020) - Guerrero, Fernando J.; Prol-Ledesma, Rosa Maria; Karimi, Nader
Abstract: The confinement of CO2 in deep geothermal reservoirs as a means of mitigation of greenhouse gas emissions is continuously motivating research on the retention capacity of these deep aquifers. An important physical containment mechanism is related with CO2 dissolution and thermo-solutal convection. In this context, numerical simulations are performed in this work to assess the effect of inclination, Rayleigh number, and buoyancy ratio on the convective transport in a rectangular porous medium. The porous enclosure is heated from below and cooled from above, whereas a solute is dissolved through the upper boundary with a constant concentration condition and no mass loss through the other boundaries. A set of governing parameters is considered in this assessment: two buoyancy ratios with dominant solute buoyant forces (10 and 100), three Rayleigh numbers (10, 50, and 80), and three inclination angles plus the horizontal case for reference (5°, 10°, and 15°). The solution to the problem is based on a Finite Volume method along with the fixed point iteration for the coupled differential equations, and a Conjugate Gradient algorithm for the algebraic system. The model is validated and tested under mesh analysis. The numerical results show that the inclination angle has a minor effect on the convective mixing properties of the porous medium in comparison with the Rayleigh number and the buoyancy ratio. Increasing the angle slightly decreases the mixing rate as a consequence of the formation of preferential flow paths associated with the inclination, these preferential flow paths make mixing less efficient and give rise to zonation of solute concentration.